ANALISIS PREFERENSI SISWA MELANJUTKANKE SMP NEGERI 7 KECAMATAN LIMA PULUH KOTA PEKANBARU TAHUN PELAJARAN 2014/2015 - Winda Aftenia Winda Aftenia; Sardi Yusuf Sardi Yusuf; Raja arlizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims: 1) To analyze the internal aspects are becoming preference choose to junior high school students, 2) To analyze the external aspects into preferences choose to junior high school students, 3) To determine the internal preference category choose to junior high school students, 4) to determine the category of external preference choose to junior high school students. The research was carried out in SMP 7 District of Fifty. Adapaun time this study was in October 2014 s / d in December 2014. This study includes a descriptive study aimed to describe and interpret the object in accordance with what it is. The sample population in this study were students SMP 7 subdistricts Fifty VII class consisting of 6 rombel totaling 250 students in Academic Year 2014/2015. In this study, researchers took 50% of the total population. To that end, the study sample was taken of students in class VII 1, VII 3, and VII 4, amounting to 125 students. Based on the analysis of research that has been done, it can be concluded: 1) Preferences choose to junior high students on the internal aspects are the desire of his own, according to their interests, and therefore in accordance with the ideals, 2) Preferences students choose to SMP is due to external aspects the approval of the parents, the basics of knowledge already learned in elementary school, and because of parents who support the high school and college, 3) Category internal preferences choose to junior high students, more than half are in the high category, 4) Category external preferences students choose to junior high school, more than half are in the medium category. Keywords: preferences